(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article presents the concept of small business, its role and importance in the sustainable development of the economy. The opinions of experts and scientists in this field are analyzed. The distinctive features of the sustainable development of small business are presented. Based on indicators such as economic, social, financial, institutional and foreign economic activity, the sustainable development of small businesses in the Andijan region is analyzed. The ways of assessing the sustainability of the industry are presented. And also, the ways of sustainable development of the small business sector of the region are proposed on the basis of the conducted research.